Law and Politics: What Is Their Relation? - Alexander,Larry (2018)
In this paper I distinguish politics-deciding what a group should do based on first-order practical reasons-and law, the norms those in the group with authority have decided should obligate those to whom the norms are addressed. I further elaborate on the distinction between rules and standards, the desirability of rules, the nature of legal interpretation, and the gap between what the legal rules may require and what all-things-considered a rule-subject should do.